Ecology of Zanthoxylum acanthopodium: Specific leaf area and habitat characteristics - DECKY INDRAWAN JUNAEDI (Society for Indonesian Biodiversity, 2019)
Abstract. Junaedi DI, Nurlaeni Y. 2019. Ecology of Zanthoxylum acanthopodium: Specific leaf area and habitat characteristics. Biodiversitas 20: 732-737.  Andaliman (Zanthoxylum acanthopodium) is an important species in North Sumatra, Indonesia either from conservation, economy, or socio-cultural point of views. Z. acanthopodium is known as plant species difficult to cultivate and its natural distribution in Indonesia is restricted to Aceh and North Sumatra, Indonesia. This study aims to identify the modest characteristics of Z. acanthopodium’s habitat in natural and cultivated areas and to assess the importance of light in these two habitat types in North Sumatra. We surveyed four districts in North Sumatra and used specific leaf area (SLA) as proxy for the importance of light in Z. acanthopodium habitat. We found that the species grow naturally in high slope areas and not in a plain area. Similarly, in cultivated areas, this species grows well in sloped area with minimum inundated surface run-off water. Z. acanthopodium with higher SLA values occurs in natural habitat and high slope areas while those with smaller SLA are found in cultivated areas and low slope although the difference is statistically not significant. This study indicates the importance of light and surface run-off for suitable habitat of Z. acanthopodium. Further studies are needed to examine the quality, intensity, and frequency of light to support Z. acanthopodium growth; and to examine the role of landscape inclination and their position relative to sun exposure (i.e. aspect) for its survival and growth rate.